Digital Gangrene an Unusual Presentation of Takayasu's Arteritis - Roy, Manoj Kumar (N Am J Med Sci, 2015)
CONTEXT: Takayasu arteritis (TA) is a chronic inflammatory disease involving large vessels like aorta and its major branches. It presents to clinician with features of arm claudication, stroke, asymmetrical pulse, or asymmetrical blood pressure in both limbs. Digital gangrene may be occurred secondary to various systemic diseases like diabetes, thrombophilic states, vascular embolism, and medium and small vessel vasculitis or infections. Through evaluation to diagnose the exact etiology and timely intervention is needed to prevent progression of the gangrene which at the time can be life-threatening. Digital gangrene as an initial presentation in TA is very rare. In medical literature, there are only few case reports have been reported. CASE REPORT: We are reporting a case of a 26-year-old female patient presented with right little finger and index finger gangrene, ultimately diagnosed as TA and responded dramatically to treatment. CONCLUSION: Though rare, TA should be taken in the differential diagnosis for work up in a case of digital gangrene and it necessitates more studies in this field to uncover the exact pathophysiology for such presentation.